High-dependency unit care after carotid endarterectomy for asymptomatic stenosis - Beatriz Carvalho Branco de Torres Guimarães (2020)
Introduction: The European Society for Vascular Surgery recommends 3-6 hours of neurological and intra-arterial blood pressure monitoring following asymptomatic carotid endarterectomy. However, only a minority of patients will benefit from prolonged monitoring in a high-dependency unit and early patient transfer to the ward could lead to significant improvement in resource management without compromising the best patient care. Aim: The main goal of the study was to identify which patients benefit the most from prolonged high-dependency unit stay. Methods: Consecutive patients submitted to carotid endarterectomy, from 2016-2017, with asymptomatic stenosis were retrospectively reviewed. To better identify patients in need of prolonged high-dependency unit stay, a composite outcome was created including cardiac events, neurologic deterioration, postoperative adrenergic/ventilatory support and prolonged use of intravenous antihypertensive therapy. Co-morbidities, anesthetic and surgical technique and monitoring variables were compared between groups. Results: A total of 58 procedures were included (84.5% male; 70±8 years) and 11 (19%) presented the composite outcome, mostly due to the need for prolonged intravenous antihypertensive therapy (n=6). The presence of diabetes was associated with higher incidence of the compositive outcome (p=0.04) and the use of acetaminophen as intraoperative analgesia demonstrated an inverse correlation with the occurrence of these events (p<0.001). Other co-morbidities, the anesthetic and surgical technique and tensional fluctuations showed no further associations. Conclusions: Diabetics are more prone to develop the composite outcome and, therefore, are the most likely to benefit from a prolonged high-dependency unit stay. The study lacks power to address other covariates. Additional studies are necessary.